Phytochemical and antibacterial properties of clove from India, Sri Lanka, and Indonesia available in Bangladesh - Hossen, Sharmin; Hossain, Irin; Akhtar, Shamim; Chowdhury, Arpita; Ahamed, Tanvir; Chowdhury, Susmita; Ahmad, Monsur (Journal of Bangladesh Academy of Sciences, 2025)
Cloves (Syzygium aromaticum) are aromatic flower buds that have been extensively studied for their culinary, medicinal, and economic value. Bangladesh has Indonesian (CIS), Indian (CID) and Sri Lankan (CSI) cloves. This study investigates the bioactive compounds, proximate analysis, physicochemical properties, and antibacterial efficacy of clove essential oils from three commercially available brands in Chattogram. Using Gas Chromatography-Mass Spectrometry (GC-MS), the primary bioactive compounds identified were eugenol, eugenol acetate, and β- caryophyllene, with significant variations in their concentrations across brands. Proximate analysis revealed differences in moisture, ash, and volatile content, highlighting disparities in quality and purity. Physicochemical properties were assessed. Antibacterial efficacy was evaluated using the agar disc diffusion method against Escherichia coli and Staphylococcus aureus and Pseudomonas aeruginosa, as indicated by its minimal inhibitory concentration (MIC) values. These findings underscore the importance of brand selection in ensuring the therapeutic and functional efficacy of clove essential oil, emphasizing the need for stringent quality control in the market. J. Bangladesh Acad. Sci. 49(2); 243-253: December 2025